The Impact of Internal Knowledge Sharing on Sales Department’s Innovativeness and New Product Commercialization - Ružić Erik; Benazić Dragan (Organizacija, 2021)
Background and Purpose: Innovativeness and new product commercialization are highly important for companies. Therefore, a deep understanding of the impact of all potentially influential drivers of success is critical. The purpose of the paper is to explore the impact of internal knowledge sharing on new product selling and sales innovativeness as well as the impact of empowerment on internal knowledge sharing and, indirectly, on new product selling and sales innovativeness.